2020
DOI: 10.1101/2020.05.19.103572
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Did I imagine that? The functional role of paracingulate cortex in reality monitoring

Abstract: Reality monitoring refers to our ability to distinguish imagination from our experiences in the outside world, and is linked both to hallucinations in schizophrenia as well as to the morphology of paracingulate cortex area of the brain. Here, we revealed less paracingulate involvement in the functional reality monitoring networks in patients with schizophrenia compared to healthy individuals. Thereafter, we used real-time fMRI neurofeedback to show that healthy individuals can learn to upregulate brain activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…During the VH condition, coherently with what always happens when the patient is hallucinating outside (as reported during the anamnesis with the neurologist), the subject was aware of the unreality of his hallucinations, suggesting a successful and preserved reality monitoring. Interestingly, the precuneus has been identified as one of the regions of interest supporting successful reality monitoring in humans [47]. In general, CBS patients do recognize the unreality of their visual hallucination [1]: this ability may be related to the fact that they were sighted people becoming blind very late in their life.…”
Section: Discussionmentioning
confidence: 99%
“…During the VH condition, coherently with what always happens when the patient is hallucinating outside (as reported during the anamnesis with the neurologist), the subject was aware of the unreality of his hallucinations, suggesting a successful and preserved reality monitoring. Interestingly, the precuneus has been identified as one of the regions of interest supporting successful reality monitoring in humans [47]. In general, CBS patients do recognize the unreality of their visual hallucination [1]: this ability may be related to the fact that they were sighted people becoming blind very late in their life.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study has demonstrated that this region causally supports reality monitoring. In healthy subjects, active real-time fMRI neurofeedback training of the paracingulate cortex has been reported to improve the reality-monitoring accuracy for imagined items as well as the functional activity of the paracingulate cortex [ 36 ]. If the relationship between the PCS morphology and the functional role of the paracingulate cortex remains unclear, taken together these findings suggest that the PCS morphology may be the structural basis for the causal role of the paracingulate cortex in reality-monitoring abilities and hallucinations.…”
Section: Discussionmentioning
confidence: 99%